Thermoluminescence and fluorescence studies of argon-implanted aluminium oxide. Issue 7 (3rd August 2019) - Nsengiyumva, S.; Chithambo, M. L.; Topic, M.; Pichon, L.
ABSTRACT: Thermoluminescence (TL) and fluorescence studies of aluminium oxide (Al2 O3 ) implanted with 80 keV argon ions at fluences in the range 1 × 10 14 –1011 × 10 16  ions/cm 2 are presented. Thermoluminescence measurements were made at 1°C/s subsequent to irradiation to 20 Gy. The glow curve consists of a prominent peak centred at 170°C, the subject of this study, and three secondary peaks of weaker intensity centred at 242, 306, and 450°C. It is observed that the TL sensitivity of the main peak decreases with fluence of implantation. This suggests that ion implantation reduces the concentration of trapping centres responsible for the thermoluminescence. Kinetic analysis carried out by means of the variable heating rate, whole glow peak and curve fitting methods shows that the activation energy of the main peak is about 1.00 eV and the frequency factor of the order of 10 10  s −1 irrespective of ion fluence. Fluorescence studies show emission bands at around 436, 676, 695 and 754 nm. These emission bands may be attributed to F 2 + -centres or Cr 3+ impurities substituting for aluminium. Scanning electron microscopy images taken from the samples indicate that their surface morphology remains the same irrespective of the implantation fluence.